Successful Therapeutic Management of Albendazole Toxicity in a Calf - Gupta, Dhiraj Kumar; Sangwan, Tanvika; Sidhu, Shabnam; Haq, Abrar Ul (International Journal of Livestock Research, 2025)
This report describes a case of albendazole toxicity in a calf presented in recumbency with the history of albendazole oral overdosing and thereafter lethargy, weakness, and recumbency. Physical examination depicted normal rectal temperature (104.5°F), congested mucus membrane, and a heart rate of 80 beats per minute. Cranial nerve dysfunction was depicted by absent menace response and pupillary light reflex at the onset of presentation. Haemato-biochemical analysis was done, which revealed anaemia, relative neutrophilia, and a disturbed liver function profile. Kidney function profile was normal, along with all electrolytes. The therapeutic management was done with Dextrose Normal saline intravenously, an antibiotic, liver tonic, and vitamin C for three days. Thereafter, the animal was active and alert with normal feed intake. Therefore, the calf was discharged from the hospital with follow-up treatment with oral liver tonic and multivitamin liquid syrup. This case emphasizes the importance of dosing precision and awareness of potential adverse effects.